Güncel Eğitim Bilimleri Araştırmaları IX (Bahar) - Özcan, Salim; Özcan, Ayniye; Pehlevan, Ercan; Çavuş, Fatma; Erdem, Aytekin; Mete, Hasan; Uzal, Gürcan; Kılıç, Erdal; Yaşar, Huriye; Karagücük, Vasıf; Sert, Serkan; Doğan, Bahar; et al. (Academician Publishing Book DOI Portal, 2024)
-